2016
DOI: 10.1515/hsz-2015-0213
|View full text |Cite
|
Sign up to set email alerts
|

De novo ceramide synthesis is involved in acute inflammation during labor

Abstract: Gestation is regulated by an inflammatory process that allows implantation and parturition. The comprehension of such inflammatory switches is important for the identification of therapeutic targets in pregnancy defects. Sphingolipids are a class of structural membrane components with important signaling functions. Among sphingolipids, ceramide is a well-known mediator of stress signals and pro-inflammatory responses. In this paper, we evaluated the association between ceramide increase and the inflammatory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…This finding supports previous reports of increased ceramide levels and expression of serine palmitoyl transferase, the rate-limiting enzyme for ceramide synthesis de novo , in the placentas of women who laboured compared with those who delivered by elective CS. This group also reported an increase in interleukin-6, suggesting the involvement of ceramide signalling and inflammatory mechanisms in labour [46]. Our data support the view that the endocannabinoid/ceramide/sphingolipid pathway has the potential to stimulate labour [40,42,46].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding supports previous reports of increased ceramide levels and expression of serine palmitoyl transferase, the rate-limiting enzyme for ceramide synthesis de novo , in the placentas of women who laboured compared with those who delivered by elective CS. This group also reported an increase in interleukin-6, suggesting the involvement of ceramide signalling and inflammatory mechanisms in labour [46]. Our data support the view that the endocannabinoid/ceramide/sphingolipid pathway has the potential to stimulate labour [40,42,46].…”
Section: Discussionsupporting
confidence: 87%
“…This group also reported an increase in interleukin-6, suggesting the involvement of ceramide signalling and inflammatory mechanisms in labour [46]. Our data support the view that the endocannabinoid/ceramide/sphingolipid pathway has the potential to stimulate labour [40,42,46].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the expression of key enzymes involved in the sphingolipid de novo biosynthesis, SPTLC1 and SPTLC2, were significantly increased, as reported in inflammatory and hypertensive [29,64,65]. Accordingly, we found a significant upregulation of SPT activity in chorionic arteries of PE compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 78%
“…It has already been demonstrated in different diseases that Cer plays a pro-inflammatory role in, for instance, airway inflammation, pulmonary edema, inflammatory bowel disease, inflammation during labor, post myocardium ischemic and cystic fibrosis [159][160][161][162][163][164][165][166][167][168]. But, the role of SLs in microglia was depicted only a few years ago when Jung and colleagues [162] showed that Cer with acyl chain length C2 to C8 was able to block the inflammation induced by LPS.…”
Section: Microglia and Sls Activation In Brain Tumormentioning
confidence: 99%